Neural responses to social exclusion in adolescents: Effects of peer status. (July 2017) - de Water, Erik; Mies, Gabry W.; Ma, Ili; Mennes, Maarten; Cillessen, Antonius H.N.; Scheres, Anouk
Abstract: We examined whether adolescents' neural responses to social exclusion and inclusion are influenced by their own popularity and acceptance and by the popularity of their excluders and includers. Accepted adolescents are highly prosocial. In contrast, popular adolescents, who are central and influential, show prosocial as well as antisocial behaviors, such as peer exclusion. Fifty-two 12–16 year-old adolescents underwent an functional magnetic resonance imaging (fMRI) scan while playing the ball-tossing game Cyberball in which they received or did not receive the ball from other virtual players. The other virtual players were described as either highly popular or average in popularity. Participants' own popularity and acceptance were assessed with peer nominations at school ( n = 31). Participants' acceptance was positively correlated with activity of the dorsal anterior cingulate cortex (ACC) during exclusion. Participants' popularity was positively associated with ventral striatum and medial prefrontal cortex activity during exclusion, but only when the excluders were popular virtual players. Participants showed increased rostral ACC activation to inclusion by players who were average in popularity. These findings indicate that peer status plays an important role in adolescents' neural processing of social exclusion and inclusion. Moreover, these findings underscore that popularity and acceptance are distinct types of high peer status in adolescence, with not only distinct behavioral correlates, but also distinct neural correlates.